Keterampilan Informasi Melalui Pembuatan Media Literasi - Ganes Gunansyah; Putri Rachmadiyanti; FX Mas Subagiyo (Publikasi Pendidikan, 2018)
Implementation of the School Literacy Movement (GLS) is still faced with a number of obstacles including: (1) literacy program still has not been socialized properly, (2) understanding of the participants on the implementation strategy literacy movements are still limited, (3) based on the analysis of the needs of teachers want practical experience integrating literacy into in learning. The obstacles are experienced by elementary school teachers in Teachers Working Group (KKG) Tosari- Pasuruan District. The purpose of this activity to facilitate a focused target groups (1) create literacy media both theory and practice conceptually, (2) the implementation strategy of literacy programs in schools. Methods of implementation of activities include the flow of activities stages, ways of working and output / outcome of community service activities. The ways of workings include (1) the distribution of material according to field of expertise, (2) mentoring  participants through brainstorming, discussion and discussion, practice simulations and demonstrations, (3) sustainable mentoring; (4) documentation of training and mentoring. While the output of activities includes (1) training module, (2) product of literacy mentoring , (3) implementation strategy design of literacy media in learning. One of the the training and mentoring results is participants has good understanding of the essence of the program School Literacy Movement (GLS) and designing procedure and create resources and literacy media, practice in creating some media literacy media like big books, mini-books, pop-up books, picture story, content posters and word wall, as well as participant delivered a high level of satisfaction with the material about training an mentoring that have been implemented.